Deviance and crime: social control, criminal justice, and criminology in Europe - Groenemeyer, Axel (GERN research paper series, 2019)
GERN (Groupement Européen de Recherches sur les Normativités) is a large consortium of scientific researchers in the domain of deviance and social control, more precisely studying delinquency, penal institutions, public policies of security and the importance of penal questions in society. Today GERN is a scientific network present in ten European countries and abroad, uniting researchers of different disciplines.00This is the fifth volume stemming from the annual doctoral conferences organized by the GERN in September 2016 in Dortmund, Germany. The selected theme for this Summer School was "Deviance and Crime - Social Control, Criminal Justice, and Criminology in Europe"; reflecting the variety of theoretical frameworks and methodologies covered by the current PhD theses in the field of criminal justice and deviance as well as fresh and new perspectives on deviant and criminal careers, on the history of restorative justice and on crime as the central theoretical concept in criminology